Evolución de los parámetros ambientales: aire, ruido y agua del 2018 al 2021 en la central de generación eléctrica de Iquitos, región Loreto - 2021 - Nuñez Ruiz, Andres Valentino (2023)
The research was carried out at the Iquitos Power Plant, in order to analyze the evolution of noise, air and water indicators and their parameters, based on environmental monitoring from 2018 -2021. The design is non-experimental, analytical, predictive, horizontal and retrospective. The secondary information was obtained from the quarterly reports of the Environmental Monitoring carried out by Electroriente. The evolution of the data from 15 quarterly environmental monitoring in their trends and prediction values was analyzed, for this the Holt-Winters Model with exponential smoothing was used. Which allowed to conclude that in the evaluation of the evolution in the indicators and their parameters: noise, air: PM-10 particulate matter, sulfur dioxide, nitrogen dioxide, hydrogen sulfide and in the effluent water: hydrogen potential (pH) , temperature (°C), electrical conductivity, dissolved oxygen and the oils and fats in the Iquitos power plant reach values below the Environmental Quality Standards, complying in all of them with D.S. No. 014-2019-EM. But, according to the predictive analysis of the indicators and their parameters for the next five monitoring sessions, these are shown to be differentiated: for noise it will decrease, in the air, for PM-10 particulate matter its levels will increase, in Carbon Dioxide sulfur, its level would increase, in Nitrogen Dioxide it would increase, in hydrogen sulfide it would remain constant, in the effluent water: in the hydrogen potential (pH) these decrease, in temperature (°C) this would decrease, in the electrical conductivity would be decreasing, in the dissolved oxygen decreasing and in the oils and fats it would not have variations.